Development and Testing of Fast Responsive Bi-Enzyme Time - Temperature Indicator. (October 2019) - Li, Qiang; Duan, Min; Li, Wen; Dai, Dai Yue; Hao, Jia; Li, Ren
Abstract: In order to directly indicate the change of the quality of temperature sensitive products, such as food and medicine, during transportation and storage, the time-temperature indicator (TTI) was researched. It has cumulative effect on the time and temperature in the transport process and also can be used to monitor the environmental temperature changes. Based on the novel glucose oxidase and horseradish peroxidase double enzyme reaction system, a new time-temperature indicator was developed. The suitable storage conditions and the composition of double enzyme asof the TTI reaction system were studied. In conclusion, the time-temperature indicator with obvious color change is applied to the packaging of cold products during the transportation and storage process.